STRATEGI BERTAHAN HIDUP PEDAGANG KAKI LIMA (PKL) DI KAWASAN WATERFRONT CITY PONTIANAK PADA MASA PANDEMI COVID-19 - Afdikal, Afdikal; Budiharto, Sutoyo; Astuty, Dwi (Universitas Tanjungpura, 2022)
This study aims to determine the survival strategy of street vendors (PKL) in the waterfront city area of Pontianak during the Covid-19 pandemic. As we know, the implementation of limited PPKM carried out by the central government and local governments to suppress the spread of the Corona virus did not have a smooth and encouraging impact for several sectors, especially the non-formal economic sector, namely street vendors. Many street vendors feel suffocated and scream because it is difficult to meet economic needs, because the policies set by the government are not in line with expected expectations. To find out the strategies used by street vendors in surviving the Covid 19 pandemic, researchers used a qualitative approach. The method used in this research is descriptive qualitative. The sampling technique used was purposive sampling technique. The method used to obtain data by means of observation, interviews, and documentation. The data analysis technique used is Miles and Huberman's interaction data analysis technique which consists of data reduction, data presentation, and conclusion drawing/verification. The results of the study indicate that in sustaining life, street vendors sell with personal capital and sometimes have to borrow from relatives. During the pandemic, some street vendors on the waterfront continued to follow the Pontianak city government's policy by using masks when selling and complying with the established curfew. However, some street vendors choose to play hide and seek with the Satpol PP, by not complying with the regulations set by the Pontianak city government. The reason street vendors continue to sell during the Covid-19 pandemic is to meet the needs of daily life. In addition, street vendors must also pay for the education of their children.